Life history and reproductive ecology of selected proteaceae in the mountain Fynbos Vegetation of the South-Western Cape - Le Maitre, David (Department of Biological Sciences, 2016)
The studies in this thesis recognise the key role of fire as a factor which has shaped the life-histories of plants in fire-prone Mediterranean shrublands. Fire regimes are not simply products of the abiotic elements of climate and ignition sources. The biotic component makes a significant contribution because community structure and processes like litter fall determine fuel loads, and fuel distribution, and will determine properties such as fire recurrence intervals and shapes and patchiness of fires. Another key factor in the evolution of the traits of fynbos plants is plant-animal interactions involving seed and seedling predators or pathogens and herbivory. Because fires have a significant random component (for example in the timing of ignition, the position of the ignition point in the landscape and in relation to the wind movements and post- and pre-fire rainfall patterns), each fire is a unique event. These random factors are overlaid on the probability distributions of the other, more predictable factors. For example both fire recurrence intervals and the seasonal fire frequencies follow predictable patterns and therefore provide a basis for natural selection. Life-history theory links the evolutionary perspective - why organisms have evolved to be the way they are - and the ecological perspective - how traits function in the current environment. The primary selective pressures in the fynbos environment are nutrient-poor soils, winter rainfall and summer drought, recurrent fires and biotic interactions. The study can be divided into four sections: (1) patterns in reproductive maturation and mortality, (2) seed bank dynamics and pre-dispersal predation by insects, (3) seed germination and seedling mortality, and (4) an analysis of the relationship between plant life-histories and fire frequency distributions. In the first study, mortality rates of Pro tea neriifolia, P. lacticolor and Leucadendrofl xanthoconus varied from 13 to 40% from the age of 1-10 years. Mortality rates from 20-30 years of age were similar in all species and significantly higher than for younger plants, providing some support for the idea that these species undergo senescence. The removal of up to 90% of the inflorescences of Pro tea lacticolor and P. nerizJolia by baboons or rodents reduced seed banks of the proteas but not LeucadendrOll xanthoconus. Seed banks at the age of 10 years, in terms of seeds per shrub were adequate for population replacement except for P. lacticolor. The studies in the second part found that the dynamics of the seed banks of Protea neriifolia and P. repens differ markedly. The number of full seeds (with a firm white embryo) declines with age in both species. Protea repens had many full seeds per inflorescence in the youngest age class, but few full seeds in older inflorescences because of seed predation by insects. Protea neriifolia had few full seeds per infloreseence but there was a slow rate of decline in the number of seeds per inflorescence. Although the number of seeds per shrub of both species declined with increasing stand density, the number of seeds per square metre increased, more than compensating for the decline in unit output. Inflorescences of P. repens experience higher levels of seed predation by insects than those of P. neriifolia. Insect infestation levels increased rapidly with increasing age in P. neriifolia but were lower in mature plants than in the co-occurring P. repens. Low and unpredictable seed set may limit the effects of seed-eating insects on the seed yield of P. neriifolia when compared with co-occurring P. repens. The third section examined the germination of planted seeds in a 28-year old shrub land. Germination and establishment before a fire in March 1987 was similar to that after the fire but seedling mortality was higher before the fire. Seedling mortality during the first summer after the fire (October to March) was significantly correlated with planting date, in contrast to the findings of a similar study in the southern Cape. Simulations using a simple empirical model based on indexes of the daily soil moisture balance and temperature showed that a reduction of 10 or 20% in daily rainfall will have little impact on the germination of seeds released in late-summer or autumn in the western Cape, because of the long wet winter period. An increase in daily temperatures could have a more significant impact as it may reduce the length of the favourable period for germination. The final study compared the life-history traits in seeders and a sprouter. Many studies have identified distinct patterns in the demography and resource alIocation patterns of seed-regenerating and sprouting plants which are analogous to the patterns predicted for semelparous and iteroparous species by life-history theory. But there are several ways in which the demography of plants in fire¬ prone environments violates the assumptions of classical life-history theory. A new approach has been developed which explicitly accommodates these deviations and provides models which predict direct relationships between the probability distribution of fires (in time) and the reproductive maturation, mortality rates and lifespans of seeders and sprouters. A test of these models using data on fire frequencies and the demography of a seed regenerating and a sprouting species of Protea shows that they appear to apply to fynbos as well. This opens the door to the development of quantitative models that can provide a consistent theoretical framework for predicting and interpreting the relationships between fire regimes and life-history traits. It also supports arguments that regeneration exclusively from seeds and by sprouting (and from seeds), and the related suites of traits, are expressions of distinct and divergent life history strategies. Why is it important to understand life-history strategies? Life-history theory is about how organisms maximise their evolutionary fitness and thus is about organisms allocate their limited resources to survival and reproduction to maximise reproductive success. The theory also provides a link between understanding what an organism is doing and when as is typically documented in demographic studies - and why it is doing that - which gives a deeper level of insight. There have been numerous studies and reviews of life-history theory which have covered a wide variety organisms, but somehow most of these studies have been based, explicitly or implicitly, on the highly simplified r-K selection models. The studies in Chapter 6 were based on an alternative model which offers new insights into the life-histories of plants in fire prone environments. The current approach to managing fynbos (e.g. how often to burn) is based on observations of plant maturation and recruitment success which are used to determine the desired intervals between fires. Studies of fire¬ frequencies also have shown that fire intervals follow a definite distribution in time. The intervals determined by these two different approaches are about the same but there has been no direct link. The new life-history based approach makes that link explicit and direct and gives us insights into why there should be a link and what the implications are. For example, what is the likely reproductive success over a range of fire frequencies. The approach still needs further development but it definitely merits further studies.